Urgensi Pengaturan Pembatasan Alat Makan Sekali Pakai dan Sedotan Plastik di SWK Surabaya - Angela Dhieta Permatasari; Yonatan Syahlendra; Martika Dini Syaputri (SAPIENTIA ET VIRTUS, 2026)
Abstract The problem of single-use plastic cutlery and straws in Surabaya's Sentra Wisata Kuliner (SWK, or culinary tourism centers) has become increasingly urgent, yet remains unregulated by the city's only relevant instrument, Surabaya Mayoral Regulation No. 16 of 2022, which governs plastic bags but not cutlery or straws. This creates a legal vacuum despite the city's obligation to support the Ministry of Environment and Forestry's target of reducing waste by 30% by 2030. This study examines (1) the extent of local government efforts to reduce single-use cutlery and straws at SWK, and (2) the urgency, from a legal-theoretical standpoint, of regulating this legal vacuum. Using a socio-legal approach, primary data were obtained through purposive-sampling interviews with environmental and cooperative-and-SME agency officials, SWK managers, vendors, and visitors, triangulated with secondary data from applicable regulations and prior studies, then analyzed descriptively-qualitatively. The findings show that while the local government has pursued general waste-reduction programs, none specifically targets single-use cutlery and straws at SWK, where vendors continue using plastic cutlery and straws mainly for reasons of cost and practicality. Applying Gustav Radbruch's theory of the purposes of law together with the precautionary and sustainable-development principles under Law No. 32 of 2009, this legal vacuum constitutes a form of regulatory failure that undermines legal certainty and environmental protection alike. This study contributes a doctrinal argument for expanding Mayoral Regulation No. 16 of 2022, or issuing a new regional regulation, to explicitly cover single-use cutlery and straws at SWK, accompanied by a tiered incentive–disincentive enforcement model.